KKN: MENGABDI, BELAJAR DAN BERTUMBUH DI PULAU TERLUAR BERSAMA MASYARAKAT DI DESA BANJARSARI KECAMATAN ENGGONO KABUPATEN BENGKULU UTARA - Riadi, Dayun; Pratama , Muhammad Irham Agung; Lestari , Meli; Olfiyani , Beti; Meldiana, Meldiana; Dewi , Anniza Purnama; Fathona , Ukhtun; Septiani , Indri; Anshori, Muhammad; Alydrus , Shafira; Pardi , Pardi; Yusril, Yusril (Inspirasi: Jurnal Pengabdian Masyarakat, 2025)
The purpose of mosque-based KKN in Banjarsari village, Enggano sub-district aims to optimize the function of the mosque as a center for religious, social and educational activities. In their activities, UIN Fatmawati Sukarno Bengkulu students implemented the Participatory Action Research (PAR) method which encourages community participation through activities of the work program of teaching ngaji, mosque cleanliness and making holy boundaries, nuzul qur'an competitions, breaking the fast with the people of Banjarsari and the lively Eid al-Fitr competition. The results of this activity show an increase in community participation, especially children and adolescents, in religious activities, a cleaner and more organized mosque environment, as well as the growth of the spirit of togetherness and collective awareness to continue to prosper the mosque as the center of community life. Each activity not only targets problem solving, but also involves the community to create a sense of ownership of the changes that occur. Awareness of collaboration between society, government, and educational institutions is the key to creating sustainable change. This KKN program is expected to be the first step in building the level of religious awareness of the community and strengthening the character of the younger generation.